Advances on P2P, Parallel, Grid, Cloud and Internet Computing : proceedings of the 14th International Conference on P2P, Parallel, Grid, Cloud and Internet Computing (3PGCIC-2019) /: proceedings of the 14th International Conference on P2P, Parallel, Grid, Cloud and Internet Computing (3PGCIC-2019). (2020) - Unknown
No abstract available